First Characterization of Kombucha Beverages Brewed in Argentina: Flavors, Off-Flavors, and Chemical Profiles - Tobías Moccia; Carolina Antuña; Clara Bruzone; Julieta Amalia Burini; Diego Libkind; Lucía Paula Alvarez (International Journal of Food Science)
Kombucha is an acidic beverage obtained through the fermentation of sweetened tea by bacteria and yeast. The kombucha market is relatively new and shows sustained growth. Given kombucha’s inherent characteristics, compliance with regulations may be challenging. The aim of this study was to characterize the chemical and sensory diversity of commercial kombuchas in Argentina. Acetic acid was the predominant acid, while lactic and glucuronic acids were present in 70% and 50% of the kombuchas, respectively. Only 20% of the kombuchas met the ethanol limit, while all fell within the established pH range. Ninety percent had sugar concentrations exceeding the limit set by Argentinian Law. As assessed by a trained panel, drinkability was positively associated with sweetness and fruity tastes and negatively associated with astringency, bitterness, and off-flavors. This work represents the first comprehensive analysis of kombuchas in Argentina, revealing their variability and providing relevant insights for producers and consumers.